Clinical Profile of Patients with Post-COVID-19 Mucormycosis at a Tertiary Care Center - S. Anju; K. A. Ameer; P. Arjun; Sujith Varghese Abraham (Journal of Advanced Lung Health)
Background: Mucormycosis is a serious but rare fungal infection, but there was an increase in incidence in the COVID-19 phase. The study aims to throw light on the possible reasons and possible treatment options for optimal outcomes. Objectives: The study aims to formulate the clinical profile of patients admitted with post-COVID-19 mucormycosis at a tertiary care center in South India. Materials and Methods: The study population included patients fulfilling the criteria for post-COVID-19 mucormycosis by histopathology examination at KIMS Health, Thiruvananthapuram, Kerala. Using data from electronic medical records, a retrospective cross-sectional study was conducted among 19 participants admitted with post-COVID-19 mucormycosis from January 2021 to December 2021. A clinical profile was identified for each patient based on age, gender, comorbidities, and risk factors. Investigations, including histopathology examination and clinical findings, were also recorded. Results: The average age of patients admitted with post-COVID-19 mucormycosis was 59 years. An important observation in the study is that all the patients had rhino-orbital involvement and were diabetic. All of them received antifungal therapy with wound debridement. Intra-cranial extension was found in all cases of mortality in this study. The most used antifungal for post-COVID-19 mucormycosis was Liposomal amphotericin B, followed by oral isavuconazole. Eighty-nine percent of the patients received glucocorticoids during COVID-19 infection. Interpretation: The prevalence of diabetes was 83% among patients in another study, whereas our study reported a 100% prevalence of diabetes among patients with post-COVID-19 mucormycosis. A mortality of 26% was reported in the present study. Conclusion: Diabetes and cerebral involvement were associated with high mortality in post-COVID-19 mucormycosis, and rhino orbital involvement was the most common form of mucormycosis in post-COVID-19 patients.